Adoption Of Green Supply Chain Initiatives By Iso 14001 Certified Manufacturing Firms In Malaysia: Key Drivers, Outcomes, And Moderating Effect Of Relationship Orientation - Khidir Eltayeb, Tarig (2009)
Isu-isu berkaitan alam sekitar sentiasa dititikberatkan oleh kerajaan, masyarakat dan organisasi perniagaan.